Sub-internal Limiting Membrane Hemorrhage Caused by Heavy Physical Activity - Vera Sumual; Nursalim, Ade John; Andrew Chietra (HM Publisher, 2024)
Sub-internal limiting membrane (sub-ILM) hemorrhage, a rare ocular condition, poses a challenge in ophthalmology due to its association with severe visual impairment. This case report presents a 27-year-old male with a sub-ILM hemorrhage following intense physical activity. Despite unsuccessful Nd:YAG laser treatments, vitrectomy with internal limiting membrane (ILM) peeling resulted in a remarkable improvement in visual acuity from hand movement to 6/6 within the first day post-surgery. The fundus photograph and OCT findings illustrated restored macular anatomy, highlighting the positive outcomes of surgical intervention.